A large multilobulated ankle swelling: rare presentation of gout - Patil, Bhushan R.; Wahegaonkar, Chandrashekhar; Agarkhedkar, Nikhil (International Journal of Research in Medical Sciences, 2016)
We are presenting a case study of a male patient presented to our outpatient department with large lobulated hard swelling in subcutaneous plane of left ankle. We found large whitish soft tissue masses. We did chemical analysis of same and it showed presence of uric acid crystals. This is a very rare presentation of gout. Upto the best of our knowledge only one such lesion has been reported from Turkey. So we wish to report this rare presentation of Gout.